Effectiveness of agricultural extension programs of selected colleges in Region I - Aquino, Remigio S. 1932- (1981)
Multiple regression analysis and t-test showed that 209 respondents out of 663 graduates of agricultural extension training programs conducted in 1976-1977 perceived the training programs to be effective in changing the clientele's knowledge, attitudes, skills and aspiration. "Before" and "after" training scores were highly significant. Six college factors (goals/objectives, organization and administrative structure, extension trainors, strategies, extension administrators and linkages) and 6 clientele factors (sex, age, education, farm size, family size and experience)are significant determinants of program effectiveness.
Mimeographed.
Thesis (Ed.D.)--University of the Philippines, Quezon City.
Vita.
Keywords: Agricultural extension work -- Philippines -- Ilocos Region; State Universities and colleges -- Philippines -- Ilocos Region